2020
DOI: 10.1164/rccm.202004-1385ed
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Ventilation in COVID-19: Interpreting the Current Epidemiology

Abstract: Right now the world is scrutinizing every cohort and every outcome for COVID-19 patients, particularly the most critically ill who are receiving mechanical ventilation. The numbers that have been published are all over the place, and some of them -such as very high mortalityare causing panic. Two major issues are at play in these epidemiological studies. The first is when to intubate, and assessment of the rates of intubation and mechanical ventilation for hospitalized patients in cohorts from across the world… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
167
1
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 200 publications
(181 citation statements)
references
References 14 publications
6
167
1
7
Order By: Relevance
“…Larger epidemiological studies have reported rates of invasive mechanical ventilation ranging from 2.3% to 33.1% of hospitalized COVID-19 patients and 29.1% to 89.9% among patients admitted to the intensive care unit (ICU). 7 Risk factors of ARDS and need for ICU admission include age >60 years, male gender and comorbidities such as heart disease, diabetes mellitus, chronic lung disease, immunocompromised state and malignancy. 3 Given that COVID-19 may cause hypoxia with minimal respiratory distress ('silent hypoxia'), the threshold for intubation should be lower particularly for those patients with persistent hypoxia despite escalation to HFNO and exhibiting shortness of breath.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Larger epidemiological studies have reported rates of invasive mechanical ventilation ranging from 2.3% to 33.1% of hospitalized COVID-19 patients and 29.1% to 89.9% among patients admitted to the intensive care unit (ICU). 7 Risk factors of ARDS and need for ICU admission include age >60 years, male gender and comorbidities such as heart disease, diabetes mellitus, chronic lung disease, immunocompromised state and malignancy. 3 Given that COVID-19 may cause hypoxia with minimal respiratory distress ('silent hypoxia'), the threshold for intubation should be lower particularly for those patients with persistent hypoxia despite escalation to HFNO and exhibiting shortness of breath.…”
mentioning
confidence: 99%
“…Table 1 provides a summary of the oxygen therapies and ventilator strategies employed by ICU globally to treat patients with COVID-19 respiratory failure. 7 Most recently, based on the results of the Randomised Evaluation of COVID-19 Therapy (RECOVERY) trial, corticosteroids (i.e. dexamethasone 6 mg per day for up to 10 days) are recommended for patients who are mechanically ventilated, and in patients who require supplemental oxygen but who are not mechanically ventilated.…”
mentioning
confidence: 99%
“…These patients usually require a prolonged period of mechanical ventilation, 3 to 4 weeks, with high mortality. 19,20 In addition to strict isolation, the risk of transmission due to droplet exposure mandates an aggressive approach to sedation and pain management to prevent sudden uncontrolled agitation and/or self extubation. The rate of unplanned extubation reported in different sedation trials, up to 12%, is unacceptably high in this context (â–șFig.…”
Section: Clinical Practice Guidelines Scope and Limitationsmentioning
confidence: 99%
“…The dynamic evolution of the pandemic provides a growing that allows for innovations to optimisations of procedures [6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Although estimates are that only 3-5% of all cases progress into critical illness [19], it is signi cant given the high numerator. Invasive mechanical ventilation is necessary for a signi cant number of COVID 19-cases, in both hospitalized and critically ill (2.3-33.1% and 29.1-89.9%, respectively) [12]. The World Health Organization (WHO) provisionally recommends ECMO in cases with refractory hypoxemia unresponsive to lung-protective ventilation emphasizing access to expertise in extracorporeal membrane oxygenation [20].…”
Section: Introductionmentioning
confidence: 99%